2022
DOI: 10.1002/jum.16065
|View full text |Cite
|
Sign up to set email alerts
|

Does Combing O‐RADS US and CA‐125 Improve Diagnostic Accuracy in Assessing Adnexal Malignancy Risk in Women With Different Menopausal Status?

Abstract: Objectives To evaluate the individual and combined performances of the Ovarian‐adnexal Reporting and Data System Ultrasound (O‐RADS US) and serum cancer antigen 125 (CA‐125) in assessing adnexal malignancy risk in women with different menopausal status. Methods This retrospective study included patients with adnexal masses scheduled for surgery based on their preoperative US and histopathology results between January 2018 and January 2020. O‐RADS were used to assess adnexal malignancy by two experienced radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Several researchers have demonstrated that O-RADS US has high reliability, with an AUC of 0.91-0.98, in predicting malignancy risk in adnexal areas [28], and those data are within the scope of the present study's data. This indicates that O-RADS US can be an effective means for the diagnosis and treatment of ovarian-adnexal masses.…”
Section: Discussionsupporting
confidence: 51%
“…Several researchers have demonstrated that O-RADS US has high reliability, with an AUC of 0.91-0.98, in predicting malignancy risk in adnexal areas [28], and those data are within the scope of the present study's data. This indicates that O-RADS US can be an effective means for the diagnosis and treatment of ovarian-adnexal masses.…”
Section: Discussionsupporting
confidence: 51%
“…A recent study [35] indicated that a combination of O-RADS, SR and CA125 had a significantly higher AUC in discriminating ovarian tumors than individual approaches, but it did not provide the specific method. Wu et al [36] developed a model of combining O-RADS and CA125, and the results suggested that the model significantly increased the diagnostic performance of malignancy risk estimation in adnexal masses. In addition, the model also showed good results in distinguishing certain subtypes of ovarian tumors.…”
Section: Discussionmentioning
confidence: 99%